2003
DOI: 10.1046/j.1523-5378.2003.00173.x
|View full text |Cite
|
Sign up to set email alerts
|

The MUC5AC Glycoprotein is the Primary Receptor for Helicobacter pylori in the Human Stomach

Abstract: Mucin MUC5AC is the most important carrier of the LeB carbohydrate structure in normal gastric tissue and forms the major receptor for H. pylori.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
113
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(119 citation statements)
references
References 50 publications
3
113
3
Order By: Relevance
“…However, only strains of H. pylori that express the BabA adhesin are capable of binding to Le b (33). Furthermore, H. pylori can bind to MUC5AC in the absence of Le b (11). In our study, there was no correlation between the ability of the H. pylori strains to bind Le b and to bind TFF1, as all strains bound to TFF1 and only one bound to Le b .…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…However, only strains of H. pylori that express the BabA adhesin are capable of binding to Le b (33). Furthermore, H. pylori can bind to MUC5AC in the absence of Le b (11). In our study, there was no correlation between the ability of the H. pylori strains to bind Le b and to bind TFF1, as all strains bound to TFF1 and only one bound to Le b .…”
Section: Discussioncontrasting
confidence: 65%
“…However, other adhesins such as the AlpA and AlpB proteins have been identified, but no receptor for these proteins has been identified (10), indicating that other receptors exist on the gastric mucosa. In addition, neither Le b nor Le x is expressed solely in the stomach, and H. pylori also binds in vitro to Le b expressed on duodenal tissue (11), which is never observed in vivo. In contrast, areas of gastric metaplasia in the duodenum can be colonized in vivo, indicating that there is a receptor for H. pylori specific for gastric tissue.…”
mentioning
confidence: 96%
“…Red fluorochromes such as TRITC or Texas-Red can be used equivalently ( Van de Bovenkamp et al, 2003), although TRITC tends to leach from bacterial cells and skew adherence profiles unless tissue sections are very thoroughly washed after the bacterial overlay. It is also important to take into consideration that bacterial surface labeling involves modification of basic amino acids and thus may diminish adherence by direct inactivation of an adhesin's binding domain or indirectly through steric hindrance.…”
Section: Characterization Of Bacterial Adherence By In Vitro Binding mentioning
confidence: 99%
“…Normal gastric mucosa shows cell type specific expression of secreted mucin MUC5AC in the surface epithelium (Wang et al, 2006;Lindén et al, 2010). Several studies have strongly suggested that MUC5AC forms the major receptor for H. pylori in the human stomach (Van de Bovenkamp et al, 2003;Lindén et al, 2008), and the infection of H. pylori can alter the expression of MUC5AC (Kocer et al, 2004).…”
Section: Introductionmentioning
confidence: 99%